Geogenic versus Anthropogenic: Hydrocarbons in the Spoil from the Falkenstein and Spering Tunnels (A9 Pyhrn Autobahn, Austria). Issue 4 (3rd August 2015) - Gratzer, Reinhard; Bechtel, Achim; Sachsenhofer, Reinhard F.; Gawlick, Hans‐Jürgen
Abstract In the Falkenstein und Spering tunnels (A9 Pyhrn Autobahn; Northern Calcareous Alps), hydrocarbon contents (HC Index) in excess of the permitted threshold values were detected in the course of the routine statutory analysis of the excavated material. Comparative detailed geochemical analysis of retained reference samples, operational consumables and core samples from boreholes drilled into the tunnel wall show that threshold values of HC indices in the Reifling Limestone are exceeded due to the presence of locally generated natural hydrocarbons. The hydrocarbons were probably formed in marly zones of the carbonate rocks and migrated into the well‐developed fracture network. These hydrocarbons are characterized by high contents of n‐alkanes, high Ts/(Ts+Tm) ratios, a predominance of C27 and C29 steranes, and the lack of oleanane. Traces of hydrocarbons in the Wetterstein Limestone contain oleanane due to contamination by operating consumables. Im Ausbruchmaterial des Falkenstein und Spering Tunnels (A9 Pyhrn Autobahn; Nördliche Kalkalpen) wurden im Rahmen der gesetzlichen Routineanalytik Überschreitungen des Grenzwerts für den Kohlenwasserstoff‐Index (KW‐Index) festgestellt. Vergleichende geochemische Detailuntersuchungen (GC‐MS, Kohlenstoff‐Isotopie) an Rückstellproben des Tunnelausbruchmaterials, an Betriebsmitteln sowie Bohrkernproben von der Strosse zeigen, dass Grenzwertüberschreitungen innerhalb der Reiflinger Kalke auf geogene Kohlenwasserstoffe zurückzuführen sind. Es handelt sich dabei vermutlich um lokal gebildetes Festbitumen, das aus den mergeligen Partien der Reiflinger Kalke in ein Kluftsystem eingewandert ist. Diese Kohlenwasserstoffe sind durch hohe Gehalte an n‐Alkanen, hohe Ts/(Ts+Tm) Verhältnisse, eine Prädominanz von C27 und C29 Steranen und das Fehlen von Oleanan gekennzeichnet. Kohlenwasserstoffspuren im Wettersteinkalk beinhalten Oleanan und sind auf Betriebsmittel zurückzuführen.